AN APPROACH TO SIMULTANEOUS WIRELESS SYNCHRONIZATION AND NAVIGATION FOR MOBILE DISTRIBUTED NETWORKS OF RADAR SYSTEMS - Kenney, Russell (My University, 2024)
Recent developments in all-digital phased arrays have probed the upper bound of performance for single monostatic radar system performance. In order for radar system performance to continue to improve beyond the current state-of-the-art, it is imperative that research into the implementation of distributed radar systems be performed as such systems will enable significant performance enhancements in comparison to traditional monostatic radars. For these systems to be implemented, particularly in mobile scenarios, both the accurate navigation and synchronization of the systems must be performed. These processes must be performed at the carrier wavelength accuracy which poses a strict requirement on the performance of the navigation and synchronization algorithms. These components have received significant attention in the literature. However, although they are closely related problems for implementing mobile distributed radar networks, the potential for implementing algorithms for simultaneous navigation and synchronization has largely been unexplored. Therefore, the research proposed in this dissertation aims to implement algorithms for simultaneous navigation and synchronization for distributed radar networks by leveraging time-of-flight (TOF) ranging signals and associated Doppler measurements. This dissertation provides a comprehensive literature review of current techniques for achieving navigation and synchronization solutions. A background is provided, describing linear and nonlinear Kalman filtering for time-series state estimation, relevant propagation effects on radio signals, a mathematical framework for inertial navigation, and the radio frequency (RF) synchronization signal model. Current research results in cooperative navigation for radar motion compensation are presented. A novel algorithm for time, phase, and frequency synchronization is described which is capable of achieving synchronization exclusively in software, enabling decentralized implementation in existing radar systems. This algorithm is provided for a single iteration of synchronization and is also adapted for the Kalman filtering of the synchronization states. A framework for combining the cooperative navigation and synchronization routines is provided along with simulated results and analysis on performance. A preliminary hardware demonstration of the synchronization algorithm is also given. Finally, a summary of future research direction and goals is provided along with a conclusion to the dissertation.
Keywords: Distributed Radar; Wireless Synchronization; Navigation; Kalman Filtering